Evaluating the Role of Celebrity Endorsements in the Success of ENDSARS Protests in Nigeria - Nwokeocha Ifeanyi Martins (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Police brutality or excessive of force by law enforcement can be legally define as a civic right violation, where law enforcement agencies officers exercise due force against a subject. Use for torture as interrogative technique and other wanton abuses of human rights remain some of the major flaws of Nigeria police force which has attracted public odium, opprobrium, and condemnation to the force. Torture described as one of the most extreme forms of violence, resulting to both psychological and physical consequences, is sometimes considered as an indispensible interrogation mechanism for mechanism for gathering strategic intelligence. Afeez(2020) worried by the incessant reports of human right abuse of the member of the police force, the former inspector-General of police, Ibrahim Idris, once warmed the special Anti-Rubbery Squad operative against torture and extrajudicial killings, saying “no policeman in the world had the right or authority to kill crime suspects.” He admonished the SARS personnel to always respect the right of every Nigerian, noting that this was the way they could change the negative public perception about them.Protest against police brutality previously have arisen in Nigeria, as advocates and researchers have documented extensive evidence of human rights abuses by SARS officers and other NPE personnel. In a 2016 report, Amnesty international asserted that SARS officer routinely committed torture and other abuses against detainees, many of whom were arrested arbitrarily, detained in communication, and forces to “confess” or pay bribes to secure release.The EndSARS movement began in 2017, as Nigerians shared experience of police brutality via social media and demonstrated in several cities to call for SARS’s dissolution. In response to those protests, the government pledged an “immediate reorganization” of SARS and an investigation into allegations against the unit. Reported abuses nevertheless persisted. In June 2020, Amnesty International remained pervasive. The 2020 End SARS protest have been noteworthy for their size, direction, and reach. Demonstration began in early October and intensified as celebrities all over the world expressed support for the protesters and as a government crackdown on marchers in mid-October provoked further demonstrations. Many activist deemed the disbanding of SARS on October 11th as inadequate, comparing it to past reforms that broadly failed to curb SARS misconducts, some also have called for broader governance improvements.Ajeez (2020) stated that as unrest continued, governors in several state have imposed curfews or banned protesters. On October 20, army and police reportedly used live fire to disperse demonstrators in Lekki and Alusa areas of Lagos, Nigerian’s commercial capital, killing several and injuring hundreds. Various world leaders criticized the crackdown; on October 22, secretary of state Micheal Pomped condemned the use of excessive force by military forces who fired on unarmed demonstrators in Lagos” calling for Nigerian security services to show maximum restraint and respect fundamental rights for demonstrators to remain peaceful.Therefore, international bodies and personalities tends to hear of this brutality in real time, because the awareness and role/ function were created by social media of which most of these international bodies participated through. Media platform handles. It is therefore upon this foundation that the society seek to examine and evaluated the role of social media in the success of EndSARS protest.